Analysis of Teachers’ Professional Competence in Strengthening Students’ Problem-Solving Skills through the Implementation of Unplugged Coding in IPAS Learning - Arditya Angga Raharja; Wakhudin (Postgraduate, University of Mataram, 2025)
Strengthening students' problem-solving abilities is a key competency in 21st-century education; however, limited access to technology in elementary schools often hinders the introduction of computational concepts. Unplugged Coding offers an alternative learning approach that trains algorithmic thinking in a simple, accessible manner. This study aims to analyze students' initial understanding, describe teachers' strategies in implementing Unplugged Coding, and assess its effectiveness in enhancing problem-solving skills. This study employed a qualitative case study design involving fifth-grade teachers and students at SDN 1 Tumiyang and SDN 1 Glempang. Data was collected through observations and semi-structured interviews, then analyzed using thematic analysis based on Polya's problem-solving framework and Brackmann's Unplugged Coding model. The findings indicate that Unplugged Coding consistently improves students' problem-solving abilities. During the problem-understanding stage, students became more capable of identifying goals and interpreting instructions logically. During the planning stage, they developed solution steps more systematically and carefully. In the implementation stage, collaboration improved along with students' ability to correct errors. In the reflection stage, students demonstrated greater skill in debugging and generating creative ideas for solving problems. The study results indicate that Unplugged Coding is effective in enhancing students' problem-solving skills through concrete activities that integrate algorithmic thinking, collaboration, and reflection. These findings suggest that this approach can serve as an innovative solution for elementary schools with limited technological resources and support the development of essential computational skills.